THE EFFECT OF LEARNER DIFFERENCES AND TEACHING OF COLLOCATION ON STUDENTS’ COLLOCATION COMPETENCE - Endah Ginanti (UIBU, 2020)
Collocation has a fairly prominent role in English Language. For non-native speakers, the years learning English does not mean non-native speakers are able to apply collocation correctly. Non-native speakers will face great difficulty in collocation because they have limited quantity of doing much exposure and their learner differences such as motivation. This current study critically reviews Mansoor Ganji’s (2012) work which investigated the influence of Gender and Years of Instruction on Iranian EFL learners’ Collocational Competence. Ganji’s found that Iranian English majors were weak in lexical collocation in spite of English had been taught at least 6 years and English teachers were blamed since they seemed not to pay enough attention to collocation teaching in Iran. This study is descriptive quantitative. The results indicates that students of nursing department at STIKES Widya Cipta Husada are also weak in collocation. However, English teachers cannot be blamed on students’ weaknesses on collocation because English teachers had taught collocation both implicitly and explicitly.